Inovasi Teknologi Informasi dan Komunikasi di Usaha Mikro Kecil Menengah Pedesaan (Adopsi Inovasi dalam Pemanfaatan Teknologi Informasi dan Komunikasi pada UMKM di Desa Sukasari, Seluma) - Indiarma, Verani (Tuturlogi: Journal of Southeast Asian Communication, 2023)
This research aims to explore the experiences of the Sukasari community in using information technology. The study was conducted in the village of Sukasari, Air Periukan District, Seluma Regency, Bengkulu. The research method used in this study is action research or participatory action research (PAR). This method is considered appropriate because it can analyze and evaluate barriers and opportunities through multidisciplinary expertise to gather information and make decisions according to the needs of the community. The results show that the Sukasari community has a general understanding of social media utilization because all the actors in the Village-Owned Enterprises (BUMDES) Sukasari have social media accounts on Facebook, Instagram, and TikTok, which they use for communication and interaction. However, the Sukasari village community also faces several challenges in the implementation of social media, such as internet accessibility, lack of understanding in creating engaging content, relationship issues, and the quality of human resources in managing social media as a means of promoting the village's potential. The Sukasari village community requires training focused on enhancing the community's skills in social media management, including content creation strategies, finding creative ideas, photo and video editing, caption creation, and even understanding the appropriate social media algorithms to create engaging and marketable social media content.